Synthesis and skin permeation study of lidocaine organic salts - Opa Vajragupta (2018)
Four organic quarternary ammonium salts of lidocaine, lidocaine adipate, lidocaine maleate, lidocaine malonate and lidocaine tosylate were prepared in this study. These compounds were regarded as prodrugs of lidocaine and were expected to enhance skin permeability by ion-pair approach. In vitro permeation study through pig skin and determination of partition coefficients were carried out. The skin permeation of lidocaine adipate and lidocaine malonate after 12 hours of application was significantly higher than lidocaine hydrochloride but was not significantly different from lidocaine (α < 0.05). The increase in permeation of organic salts from lidocaine hydrochloride and the different profile of permeation from lidocaine may be the result of prodrug structure contributing ion-pair transportation beside normal route of transportation. © 1994 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.